PENGARUH SUHU KALSINASI TERHADAP UKURAN KRISTAL DAN KOMPOSISI FASA PADA SENYAWA TiO2 - Amos Tigor Tobing; Dina Kartika Maharani (Unesa Journal of Chemistry, 2021)
TiO2 or commonly called Titanium dioxide is a semiconductor transition metal. This metal is commercially shaped white powder. This material is often used in research into the development of photocatalysts effects in material. TiO2 is used in paints as compounds that give rise to self-cleaning properties. This property is the nature of a material to clean itself from impurities. Self cleaning works with the help of the photocatalyst effect, which is where with the help of photon energy. Therefore semiconductor material can be used in these properties. This is because Titanium dioxide is a semiconductor compound which has a band gap energy of 3.2 eV for the anastase phase, and for the rutile phase of 3.0 eV. This study aims to determine the effect of calcination temperature on the characteristics of TiO2 compounds. In this research, TTiP is a precursor of TiO2 synthesis, and the method used is the sol-gel method. After synthesis, TiO2 is calcined at 400°C, 450°C, 500°C, and 550°C. The characterization carried out in this research is to use the Fourier Transform Infra Red (FTIR) instrument that functions to determine the functional groups formed and the X-Ray Diffraction (XRD) instrument which functions to determine the phase composition of the compound. From the research that has been carried out obtained functional groups -OH, Ti-O, and Ti-O-Ti. This shows that TiO2 was successfully formed through the sol-gel method. In the phase analysis, the results showed that TiO2 is in the anastase phase. This shows that TiO2 can function well when applied to photocatalysts Keywords: Titanium Dioxide (TiO2), Calcination Temperature, photocatalysts, Self cleaning